Analisis Ekualisasi SPT Masa PPN Dengan SPT PPh Badan Terhadap Kewajiban Perpajakan PT. Adiyana Teknik Mandiri - Pratama, Irham Firdauza; Sutomo, Hadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
Many cases are related to corrections caused by the occurrence of VAT and Income Tax equalization. The difference in reporting the circulation of business on the VAT SPT with the Corporate Income Tax Return is the object of the tax authorities' examination. Basically, equalization is not to find the same number of circulation businesses but to find the cause of the difference between the VAT Period of Income Tax and the Corporate Income Tax Return. These differences are often due to differences in provisions between Income Taxes and Value Added Taxes, such as tax objects, exchange rates, and so on. The purpose of this study was to find out how to report the circulation of business between the VAT Period of VAT and Corporate Income Tax Returns of PT. AdiyanaTeknikMandiri. To find out the process and analysis of equalization between VAT Period of VAT and Corporate Income Tax Returns at PT. AdiyanaTeknikMandiri. To find out the equalization benefits of the VAT Period SPT with Corporate Income Tax Returns for companies. This study uses a comparative descriptive method with qualitative and quantitative data, namely by analyzing and processing financial statement data and existing fiscal reports, then comparing the circulation of business to the results of calculations according to the VAT Period of VAT and Corporate Income Tax Returns, then processed further to provide an explanation of the difference in business circulation generated. The results of this study indicate that PT. AdiyanaTeknikMandiri that the company in reporting the circulation of its business has not been reported as it should, it is known after equalizing it is known that there is a number of business circulation that has not been reported in the VAT Period SPT report so that it causes a difference in the amount of business circulation between the VAT Period of Income Tax and the Corporate Income Tax Return. Equalization process is carried out by comparing the VAT Period report with the Corporate Income Tax Return, collecting data on business circulation in the ledger, comparing the data obtained, then analyzing the factors that cause the different reporting of business circulation. Equalization benefits for the company, which can be a preventive measure to face a tax audit by the tax authorities, so that the company can explain in accordance with the conditions that occur, equalization can also be a benchmark of compliance and increase the accuracy of taxpayers in reporting the amount of tax obligations in accordance with the applicable law . Keywords: tax equalization, business circulation, corporate income tax return